PAINFUL OPHTHALMOPLEGIA IN CAROTID-CAVERNOUS FISTULA - Wino Vrieda Vierlia; Seskoati Prayitnaningsih (Journal of Pain, Headache and Vertigo, 2022)
Ophthalmoplegia is defined as a consequence of multiple cranial nerve paralysis innervated the extraocular muscles. The impairment of ophthalmic branch of trigeminal nerve will create a painful condition. Numerous underlying mechanism have been proposed related to painful ophthalmoplegia and carotid-cavernous fistula is one of the main causes with sight and life threatening outcome if left untreated. Carotid-cavernous fistula arises as an abnormal communication between carotid artery and cavernous sinus. Important signs and symptoms of carotid-cavernous fistula may include red eye, proptosis, painful ophthalmoplegia, headache and vision loss. Neuroimaging and angiography are mandatory in diagnosing the disease. Systematized approach and early recognition to the evaluation of carotid-cavernous fistula will lead to prompt management in avoiding morbidity and mortality in severe cases.